Little Millet - Nandini, C.; Vetriventhan, Mani; Joshi, D.C.; Maharajan, Theivanayagam; Nandini, B.; Bhat, Sujata; Meenakshi, J.; Parveen, Gazala S.; Nagaraja, T.E.; Divya, M.; Ceasar, Stanislaus Antony (Springer, 2025)
Little millet (Panicum sumatrense) is an important crop of the Poaceae family, originating from India, and is predominantly cultivated in marginal soils with minimal input. This crop is highly nutritious and resilient to climate change, offering substantial potential to bolster food and nutrition security. Two cultivated races of little millet are nana and robusta. A considerable variability has been conserved in various gene banks. Utilizing this diversity is crucial for crop improvement. Improved little millet genotypes are developed through primary selection from landraces, while hybridization techniques are currently being explored for the new varieties development and release. Evaluating germplasm for different traits and employing genomic tools could expedite the development of improved cultivars that are high-yielding, nutrient-rich, and stress-tolerant. Phenotypic evaluation of landraces for various traits and use of genomic tools could accelerate the development of improved cultivars with high yield, nutrient density, and stress tolerance. Little millet may play a significant role in food security as the need for nutrient-dense and climate-adaptive crops grows globally. However, greater consumer awareness, regulatory support, and targeted breeding techniques are required for wider adoption. Highlight of this chapter is a comprehensive view on the significance of little millet as a nutritious food, along with its origin, history, genetic resources, breeding, genomics, cropping system, value addition, etc. Such insights will assist researchers in developing high-performing genotypes with enhanced tolerance to biotic and abiotic stresses, as well as in leveraging advanced genomic tools for this underutilized crop.